The European multistakeholder PanCareFollowUp project: novel, person-centred survivorship care to improve care quality, effectiveness, cost-effectiveness and accessibility for cancer survivors and caregivers - van Kalsbeek, Rebecca J; van der Pal, Helena J H; Hjorth, Lars; Winther, Jeanette F; Michel, Gisela; Haupt, Riccardo; Uyttebroeck, Anne; O'Brien, Kylie; Kepakova, Katerina; Follin, Cecilia; Muraca, Monica; Kepak, Tomas; et al. (European journal of cancer (Oxford, England, 2021)
BACKGROUND: The majority of childhood cancer survivors are at risk of treatment-related adverse health outcomes. Survivorship care to mitigate these late effects is endorsed, but it is not available for many adult survivors of childhood cancer in Europe. The PanCareFollowUp project was initiated to improve their health and quality of life (QoL) by facilitating person-centred survivorship care. METHODS: The PanCareFollowUp consortium was established in 2018, consisting of 14 project partners from ten European countries, including survivor representatives. The consortium will develop two PanCareFollowUp Interventions, including a person-centred guideline-based model of care (Care Intervention) and eHealth lifestyle coaching (Lifestyle Intervention). Their development will be informed by several qualitative studies and systematic reviews on barriers and facilitators for implementation and needs and preferences of healthcare providers (HCPs) and survivors. Implementation of the PanCareFollowUp Care Intervention as usual care will be evaluated prospectively among 800 survivors from Belgium, Czech Republic, Italy and Sweden for survivor empowerment, detection of adverse health conditions, satisfaction among survivors and HCPs, cost-effectiveness and feasibility. The feasibility of the PanCareFollowUp Lifestyle Intervention will be evaluated in the Netherlands among 60 survivors. RESULTS: Replication manuals, allowing for replication of the PanCareFollowUp Care and Lifestyle Intervention, will be published and made freely available after the project. Moreover, results of the corresponding studies are expected within the next five years. CONCLUSIONS: The PanCareFollowUp project is a novel European collaboration aiming to improve the health and QoL of all survivors across Europe by developing and prospectively evaluating the person-centred PanCareFollowUp Care and Lifestyle Interventions.
Keywords: Empowerment; Patient-centred care; Shared; přežívající onkologičtí pacienti; Europe; osoby pečující o pacienty; Neoplasms; Quality of Health Care; Aftercare; lidé; Evropa; Caregivers; Cancer Survivors; Survivorship; Quality of life; Practice guideline; Cancer survivors; Decision-making; období po vyléčení; kvalita zdravotní péče; Humans